Díaz Lacayo, Aldo. (2015) La Guerra Nacional: Omisiones históricas. Managua: Aldilá - Gaitán Lugo, Luis Javier (Universidad Nacional Autónoma de Nicaragua, Managua. UNAN-Managua, 2017)
Revista Humanismo y Cambio Social. Número 7. Año 3. Enero - Junio 2016: 134-135